Analysis of hospital food services to improve food intake among inpatients - Hanani Abriani Sartika; Saimi Saimi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Excessive food waste in hospital inpatient wards represents a serious concern, potentially indicating dissatisfaction among patients regarding the meals served. This issue not only undermines the efficiency of nutrition services but may also hinder the patient's recovery process. Purpose: To analysis of hospital food services to improve food intake among inpatients. Method: An analytical observational design using a cross-sectional approach was applied. From a population of 952 individuals, a total of 90 participants were selected as sample. Data were collected through a validated questionnaire (p < 0.05), and reliability was confirmed using Cronbach’s Alpha (≥ 0.7), indicating strong consistency. Data were analyzed using chi-square tests for bivariate analysis and multiple logistic regression for multivariate analysis. Results: Improved friendliness among nutrition staff significantly reduced food waste, with an effect size of 7.122 times. This underscores the critical role of interpersonal interactions in nutrition services. Enhanced food presentation increased patient consumption or decreased food waste by 28.451 times, with a regression coefficient of 3.348, highlighting the importance of food aesthetics and appeal. The accuracy of nutritional content and calorie levels reduced food waste by 16.873 times (regression coefficient = 2.826), confirming the impact of appropriate nutritional composition. Moreover, patients with a more positive attitude were 2.585 times more likely to consume their meals, as indicated by a regression coefficient of 0.950. Conclusion: This study demonstrates that the friendliness of nutrition staff significantly contributes to the success of hospital nutrition services and improves patient satisfaction. Elements of food presentation—including appearance, aroma, temperature, and texture—also play a pivotal role in encouraging patients to eat. Furthermore, providing meals with accurate nutritional value and fostering positive attitudes in patients enhances the effectiveness of nutritional interventions and supports the healing process during hospitalization.